Persepsi Petani Terhadap Penerapan Teknologi Konservasi Lahan pada Budidaya Padi di Kecamatan Nagrak Kabupaten Sukabumi - Destiani; Kusmiyati; Tri Ratna Saridewi (Politeknik Pembangunan Pertanian Bogor, 2022)
According to data from statistics, the productivity of paddy (Oryza sativa L.) in the sub-district of Nagrak has decreased. One of the causes is the decline in land quality due to the lack of positive perceptions of farmers on the application of land conservation technology. This study aims to determine farmers' perceptions of the application of land conservation technology in lowland rice cultivation, analyze the factors that influence farmers' perceptions, and formulate extension strategies so that farmers have positive perceptions of the application of land conservation technology. The study used descriptive analysis and factorthe ial method. Based on the results of the study on 60 respondents, it shows that most of the farmers' perceptions, in general, are neutral, namely the application of land conservation technology has benefits for the environment but not economically and not by the habits of farmers. The factors that significantly influence the perception of farmers to consist of a length of education, the role of farmer groups, and the role of agricultural extension. The strategy to improve farmers' perceptions consists of optimizing the role of agricultural extension and farmer groups through the implementation of extension on land conservation technology in farmer groups as an effort to increase the capacity of farmers.